Solution representations for Trefftz-type finite elements - Piltner, Reinhard (Computer Assisted Methods in Engineering and Science, 2003)
Solution representations are available for several differential equations. For elasticity problems some of the solution representations are considered in this paper. The solution representations can be used for a systematic construction of Trefftz functions for the derivation of Trefftz-type finite elements. For the example of a thick plate a set of Trefftz functions is presented.